Collaborative curriculum design in the context of financial literacy education - Boukje Compen; Wouter Schelfhout (Journal of Risk and Financial Management, 2021)
Financial literacy education is being integrated into school curricula at an increasing frequency. However, the majority of teachers lack the required competencies and teacher self-efficacy to effectively teach financial topics. In this study, we evaluated whether participation in teacher design teams (TDTs) results in high-quality educational materials, encouragement of professional learning, and ultimately, enhanced teacher self-efficacy in the face of pending curriculum reform. We conducted an exploratory multiple-case study in Flanders, Belgium. Data were collected from two TDTs that developed materials aligning with the financial literacy learning standards. We observed the team meetings and conducted interviews with the participating teachers and the team coach. Our results suggest that participation in TDTs supports the three outcome variables that we examined. However, they also revealed that each outcome shows room for improvement. Furthermore, the data provided additional evidence for the importance of meeting several input and process factors that had been previously shown to be essential for effective TDT function.
Keywords: 330; collaborative curriculum design; financial literacy education; teacher design team